Empowerment in Practice : From Analysis to Implementation - Alsop, Ruth; Bertelsen, Mette; Holland, Jeremy (Washington, DC: World Bank, 2012)
This book represents an effort to present an easily accessible framework to readers, especially those for whom empowerment remains a puzzling development concern, conceptually and in application. The book is divided into two parts. Part 1 explains how the empowerment framework can be used for understanding, measuring, monitoring, and operationalizing empowerment policy and practice. Part 2 presents summaries of each of the five country studies, using them to discuss how the empowerment framework can be applied in very different country and sector contexts and what lessons can be learned from these test cases. While this book can offer only a limited empirical basis for the positive association between empowerment and development outcomes, it does add to the body of work supporting the existence of such a relationship. Perhaps more importantly, it also provides a framework for future research to test the association and to prioritize practical interventions seeking to empower individuals and groups.